Disruption of A2AR-D2R Heteroreceptor Complexes After A2AR Transmembrane 5 Peptide Administration Enhances Cocaine Self-Administration in Rats - Borroto-Escuela, Dasiel O.; Wydra, Karolina; Li, Xiang; Rodriguez, David; Carlsson, Jens; Jastrzębska, Joanna; Filip, Malgorzata; Fuxe, Kjell (Springer, 2018)
Antagonistic allosteric A2AR-D2R receptor-receptor interactions in heteroreceptor complexes counteract cocaine self-administration and cocaine seeking in rats as seen in biochemical and behavioral experiments. It was shown that the human A2AR transmembrane five (TM5) was part of the interface of the human A2AR-D2R receptor heteromer. In the current paper, the rat A2AR synthetic TM5 (synthTM5) peptide disrupts the A2AR-D2R heteroreceptor complex in HEK293 cells as shown by the bioluminescence resonance energy transfer method. Rat A2AR synthTM5 peptide, microinjected into the nucleus accumbens, produced a complete counteraction of the inhibitory effects of the A2AR agonist CGS21680 on cocaine self-administration. It was linked to a disappearance of the accumbal A2AR-D2R heteroreceptor complexes and the A2AR agonist induced inhibition of D2R recognition using proximity ligation assay and biochemical binding techniques. However, possible effects of the A2AR synthTM5 peptide on accumbal A2AR-D3R and A2AR-D4R heteroreceptor complexes remain to be excluded. Evidence is provided that accumbal A2AR-D2R-like heteroreceptor complexes with their antagonistic receptor-receptor interactions can be major targets for treatment of cocaine use disorder.
Keywords: Dopamina - Receptores; Receptores; Adicción; Addiction; Dopamine D2R receptor; Adenosine A2A receptor; Peptide Administration; Heteroreceptor Complexes; Allosteric modulation; Cocaine Self-Administration; Receptor-receptor interactions